EMPLOYEE PERFORMANCE ANALYSIS AT THE SUNGKAI TENGAH SUBDISTRICT OFFICE, NORTH LAMPUNG REGENCY - Yudhi Stiawan; Agus Purnomo (International Journal of Multidisciplinary Reseach, 2026)
This study analyzes employee performance at the Sungkai Tengah Subdistrict Office, North Lampung Regency. The research was motivated by the strategic role of subdistrict employees in delivering public services and by preliminary indications of administrative delays, uneven coordination, and limited use of administrative technology. The study used a qualitative descriptive approach with data collected through interviews, observation, and documentation. The analysis applied employee performance indicators consisting of work quality, work quantity, cooperation, responsibility, and initiative, while also identifying supporting and inhibiting aspects of performance implementation. The findings show that employee performance is generally good. Work quality, work quantity, and responsibility are categorized as good, whereas cooperation and initiative are fairly good and still require improvement. Supporting aspects include employee work ability, motivation, discipline, a conducive work environment, available facilities, and leadership support. Inhibiting aspects include administrative delays, uneven technological capacity, workload imbalance, limited inter-unit coordination, and different levels of employee experience.